2004
DOI: 10.1097/01.ccm.0000127262.16690.65
|View full text |Cite
|
Sign up to set email alerts
|

Family satisfaction with family conferences about end-of-life care in the intensive care unit: Increased proportion of family speech is associated with increased satisfaction*

Abstract: This study suggests that allowing family members more opportunity to speak during conferences may improve family satisfaction. Future studies should assess the effect of interventions to increase listening by critical care clinicians on the quality of communication and the family experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
249
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(265 citation statements)
references
References 29 publications
7
249
0
9
Order By: Relevance
“…[17][18][19][20] In our study, practitioners verbally dominated family meetings talking substantially more than actorfamily members (70 vs 30%). Our results using realistic enactments are strikingly consistent with the findings of McDonagh et al, 21 who reported that in actual end-of-life conferences in adult intensive care units (ICUs), clinicians spoke 71% and family members 29% of the time. Greater opportunity for family members to speak in ICU family meetings has been positively associated with family satisfaction and less conflict with staff.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[17][18][19][20] In our study, practitioners verbally dominated family meetings talking substantially more than actorfamily members (70 vs 30%). Our results using realistic enactments are strikingly consistent with the findings of McDonagh et al, 21 who reported that in actual end-of-life conferences in adult intensive care units (ICUs), clinicians spoke 71% and family members 29% of the time. Greater opportunity for family members to speak in ICU family meetings has been positively associated with family satisfaction and less conflict with staff.…”
Section: Discussionsupporting
confidence: 91%
“…Greater opportunity for family members to speak in ICU family meetings has been positively associated with family satisfaction and less conflict with staff. 21 The unequal proportion of family-to-practitioner speech observed in our study highlights an area of clinical practice worthy of further exploration and improvement. Analysis of the content of the conversations revealed that practitioners, especially physicians, devoted most of their statements to providing biomedical information.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…37,40 Others have since demonstrated that this involves listening more and speaking less. 41 while ensuring management plans are shared with all members of the multidisciplinary team. 42 The multidisciplinary team approach has been shown to benefit patients with acute brain injury, both acutely 43 and during rehabilitation.…”
Section: Relationships With Patients and Familiesmentioning
confidence: 99%
“…Among the many potential contributors to these adverse bereavement outcomes are the circumstances surrounding and processes of limiting life support. This hypothesis is supported by evidence that ICU deaths are commonly preceded by decisions to withdraw life support [3], and evidence that both ICU processes of care [4,5] and behaviors of ICU clinicians [1,6] near the end of life can influence family members' post-ICU psychological outcomes. Thus, uncertainty regarding which approaches to withdrawing mechanical ventilation are least distressing for patients and families [7,8] represents an important area for rigorous investigation.…”
mentioning
confidence: 94%